2016
DOI: 10.1108/ijtc-12-2015-0031
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the influence of electronic word of mouth on visit intention: the mediating role of tourists’ attitude and city image

Abstract: Purpose – The purpose of this paper is to investigate how electronic word of mouth (e-WOM), attitude, and city image affect tourists’ intention to visit a tourism city. Design/methodology/approach – Drawing from the tourism management literature, the authors hypothesize and test the relationships among e-WOM, attitude, overall city image, and visit intentions. Structural equation modeling was conducted to test the proposed relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
61
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 43 publications
13
61
0
10
Order By: Relevance
“…At the same time, the development of online tourism services has made eWOM increasingly more important for the tourism industry. EWOM provides abundant information support for tourists' decision‐making and destination marketing (Jacobsen & Munar, ; Sparks & Browning, ), affecting tourists' travel intentions (Doosti et al, ), destination selection (Jalilvand & Samiei, ), and destination impression and trust (Baka, ; Mohammed Abubakar, ). This makes research of eWOM particularly important.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the development of online tourism services has made eWOM increasingly more important for the tourism industry. EWOM provides abundant information support for tourists' decision‐making and destination marketing (Jacobsen & Munar, ; Sparks & Browning, ), affecting tourists' travel intentions (Doosti et al, ), destination selection (Jalilvand & Samiei, ), and destination impression and trust (Baka, ; Mohammed Abubakar, ). This makes research of eWOM particularly important.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research shows that eWOM can provide substantive information support for tourists' decision‐making and destination marketing (Jacobsen & Munar, ; Sparks & Browning, ). For example, eWOM can influence tourists' travel intentions (Doosti, Jalilvand, Asadi, Pool, & Adl, ), the choice of destination (Jalilvand & Samiei, ), and impression and trust towards the destination (Baka, ; Mohammed Abubakar, ). Previous studies have focused on examining the effect of eWOM on tourism, whereas factors motivating tourist involvement in eWOM communication have received few attention (Bronner & de Hoog, ; Munar & Jacobsen, ), especially when comparing eWOM motivations on different types of platform.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that travel intention has a significant positive effect on travel decisions. Doosti et al, (2016) conducted a study in pool city, Iraq, where the results showed e-WOM has a significant positive effect on travel intention, city image, and attitude toward the city. He also found city image and attitude testing on travel intention and travel decision.…”
Section: Introductionmentioning
confidence: 99%
“…He also found city image and attitude testing on travel intention and travel decision. Referring to Doosti et al, (2016) and Sari & Pangestuti (2018), who discussed e-WOM as an antecedent variable, it is interesting to study further. The purpose of this study is to examine the effect if e-WOM (social media Instagram) on city image, attitude, travel intention, and travel decision.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil ini mengonfirmasi definisi perilaku konsumen menurut Sumarwan (2004:26) yang menyatakan bahwa semua kegiatan, tindakan, serta proses psikologis yang mendorong tindakan tersebut pada saat sebelum membeli, ketika membeli, menggunakan, menghabiskan produk dan jasa setelah melakukan hal-hal tersebut atau kegiatan mengevaluasi. Selain itu, hasil ini sesuai dengan penelitian yang dilakukan oleh Abubakar et al (2017), Doosti et al (2016) Hipotesis kedua bertujuan untuk menjelaskan pengaruh e-WOM terhadap citra destinasi obyek wisata Taman Edelweis Bali. Berdasarkan hasil analisis, dapat disimpulkan variabel e-WOM berpengaruh positif dan signifikan terhadap variabel citra destinasi obyek wisata Taman Edelweis Bali.…”
Section: Gambar 2 Diagram Koefisien Jalur E-wom Terhadap Niat Berkununclassified